PRIOR TO SCHOOL EDUCATION IN ORGANIZATIONS EDUCATIONAL CORRECT ORGANIZATION OF ACTIVITY THE IMPORTANCE OF MATURITY - Ergasheva Nodira Ulug`bek daughter (American Journals, 2024)
This in the article state and non-state before school education in organizations each one group in the section educational of activities right organize of doing importance and him in the child's life place about word held.
Keywords: Activity, health marriage style, behavior, hygiene, analysis.